Harta Bersama dalam Sistem Kewarisan Islam: Perspektif Gender terhadap Hukum Islam Klasik - Ferdian Ferdian; Muliadi Muliadi; Firmansyah Firmansyah; Nanta Septia; Illian Hikma (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
Women's contribution to household economic development has become increasingly significant; however, classical Islamic inheritance law does not yet accommodate the concept of jointly acquired property fairly. In classical fiqh, inheritance is distributed without considering the productive role of wives during marriage, leading to gender-based inequality in practice. This study aims to examine the position of jointly acquired property within the classical Islamic inheritance system and evaluate to what extent it reflects gender justice. Using a library research method with a normative-theological approach and a gender perspective, this study finds that classical inheritance law positions wives solely as heirs, not as rightful co-owners of marital property. As a result, women's economic rights are often marginalized after the death of their husbands. A normative reinterpretation of fiqh is therefore necessary, utilizing the framework of maqāṣid al-sharī‘ah, particularly the principles of justice (al-‘adl) and public interest (al-maṣlaḥah), to include joint property as a form of substantive justice. This finding encourages Islamic legal reform to be more responsive to social realities and gender equality.